The growth phenomenon: An analysis - Hugh G. Clarke (South African Journal of Business Management, 1982)
The author maintains that growth - biological, physical, economic - is concerned with the transformation of one form of energy and matter into another. He analyses the way this energy is used and relates this to business growth. Energy utilization, entropy, transformation and maintenance costs, and the need to seek energetic efficiencies, are discussed. In his analysis of the mechanics of growth, and especially the sigmoid curve, the author shows with examples that a characteristic of growth is that success tends to develop the seeds of failure: that one characteristic of normal developmental growth is the restriction imposed on that growth by the organisms or organization's genus. Business failure is seen as inevitable as the 'natural' ageing process and the author examines critical periods in which the business may fail. He concludes by examining strategies for prolonging business 'life' and urges greater multi-disciplinary research into the life process.
Keywords: 650